2016
DOI: 10.1089/gtmb.2015.0241
|View full text |Cite
|
Sign up to set email alerts
|

Association Between a Glucokinase Regulator Genetic Variant and Metabolic Syndrome in Taiwanese Adolescents

Abstract: The GCKR rs780094 polymorphism is associated with low HDL-C levels and MetS incidence in Taiwanese adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…Previous reports demonstrated the role of GCKR rs780094 polymorphism in dyslipidemia, high triglyceride level and impaired fasting glucose (30)(31)(32). In a study, in Taiwan the association between GCKR rs780094 and MetS and HDl-C has been reported among adolescents (33).…”
Section: Discussionmentioning
confidence: 92%
“…Previous reports demonstrated the role of GCKR rs780094 polymorphism in dyslipidemia, high triglyceride level and impaired fasting glucose (30)(31)(32). In a study, in Taiwan the association between GCKR rs780094 and MetS and HDl-C has been reported among adolescents (33).…”
Section: Discussionmentioning
confidence: 92%
“…The rs780094 polymorphism in GCKR is strongly associated with elevated triglyceride concentrations and metabolic syndrome . In addition, the T allele of rs780094 is associated with a decreased risk of susceptibility to T2DM in certain populations .…”
Section: Introductionmentioning
confidence: 99%
“…As in the present study in the Iranian population, CT genotypes of the three SNPs were associated with lower HDL-C levels. In another study where the participants were Taiwanese Adolescents, T-allele carriers of rs780094 were more highly represented among participants with low HDL-C levels [42].…”
Section: Discussionmentioning
confidence: 94%